PENGARUH PEMBELAJARAN MATEMATIKA REALISTIK TERHADAP KEMAMPUAN MATEMATIS SISWA (DITINJAU DARI KEMAMPUAN REPRESENTASI DAN KOMUNIKASI) - Hidayatul Purnama Ariyanti (Universitas PGRI Adi Buana Surabaya, 2016)
This research is motivated by the low mathematical ability of students seen in the test results Programme for International Student Assessment (PISA) in 2012. The ability of mathematics not only be based on the ability of understanding only, but there are also other capabilities that factor into the level of mathematical ability of students, among others, representation and communication capabilities. So to overcome this use realistic mathematics learning. Formulation of the problem in this research is